2003
DOI: 10.1161/01.str.0000085085.20390.a3
|View full text |Cite
|
Sign up to set email alerts
|

Levels of α 1 -Antitrypsin in Plasma and Risk of Spontaneous Cervical Artery Dissections

Abstract: Background and Purpose-Abnormalities of dermal connective tissue have been detected in patients with spontaneous cervical artery dissections (sCAD), suggesting an underlying structural defect of the arterial wall. ␣ 1 -Antitrypsin (A1-AT) is a circulating serine proteinase inhibitor of proteolytic enzymes that helps to maintain the integrity of elastic and collagen fibers. Methods-To test the hypothesis that moderate deficiency of A1-AT may be a risk factor for sCAD, 22 cases with sCAD and 113 controls were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 10 publications
1
35
0
2
Order By: Relevance
“…It has been associated with major head and neck trauma 4 as well as with minor trauma secondary to a wide range of insults. 5 Other risk factors proposed include recent infection, 6 hyperhomocysteinemia, 7-9 migraine, 10 low levels of ␣1-antitrypsin, 11 and hypertension [12][13][14] and fibromuscular dysplasia, 15 but most evidence is limited. 16 Several arguments suggest genetic factors may play an important role in the pathophysiology of CAD, in rare cases as part of a single gene disorder and more commonly as part of a multifactorial predisposition (Figure 1).…”
mentioning
confidence: 99%
“…It has been associated with major head and neck trauma 4 as well as with minor trauma secondary to a wide range of insults. 5 Other risk factors proposed include recent infection, 6 hyperhomocysteinemia, 7-9 migraine, 10 low levels of ␣1-antitrypsin, 11 and hypertension [12][13][14] and fibromuscular dysplasia, 15 but most evidence is limited. 16 Several arguments suggest genetic factors may play an important role in the pathophysiology of CAD, in rare cases as part of a single gene disorder and more commonly as part of a multifactorial predisposition (Figure 1).…”
mentioning
confidence: 99%
“…10,11 Vila et al recently showed that A1-AT plasma concentrations less than 90 mg/dl were associated with spontaneous cervical artery dissections regardless of age, sex, or vascular risk factors. 12 The family history of the present patient does not support this diagnosis, but measurement of her serum concentration of A1-AT and genetic diagnosis may have been helpful. The differential diagnosis includes any abnormalities in the type I collagen molecules, such as the defect of fibrillin in Marfan syndrome, 13 the COL3A1 gene in Ehlers-Danlos syndrome type IV, 14 and lysyl hydroxylase in Ehlers-Danlos syndrome type VI.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have reported the involvement of various combinations of nerves (6,15), however, at present, there are a limited number of studies that describe ICADs manifesting as space-occupying lesions with skull base erosion (21). The present study suggests that, for patients with single or multiple space-occupying lesions of the skull base and end-group cranial nerve palsy, a differential diagnosis should be established from malignant skull base tumors, schwannoma, soft meningioma, infectious diseases and spontaneous diseases (9).…”
Section: Discussionmentioning
confidence: 73%